2005
DOI: 10.1007/s10897-005-0641-5
|View full text |Cite
|
Sign up to set email alerts
|

Racial‐Ethnic Differences in Genetic Amniocentesis Uptake

Abstract: The objective of this study was to determine the role of health beliefs in genetic amniocentesis acceptance in a diverse racial-ethnic population. Participants completed a previously-validated questionnaire consisting of three sections: (1) demographics, (2) amniocentesis knowledge, and (3) health beliefs, which assessed perceived susceptibility, seriousness of potential impact, benefits of testing, and barriers to testing. The results showed that Hispanic women were less likely to accept amniocentesis (51.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…Therefore, this study confirms the importance of nationality, education and socioeconomic status as predictors of adequate knowledge of prenatal diagnostic procedures as has been shown in previous studies [11,19,28,29] . Our results also indicate that women from minority ethnic groups and low socioeconomical status did not have negative attitudes towards genetic testing, but rather lower rates of informed choice, as has been previously reported [14,30,31] . It is noteworthy that among the 354 women who were interviewed, 252 (71.2%) were already aware of amniocentesis or CVS before the present gestation via friends, TV/press or due to family history.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, this study confirms the importance of nationality, education and socioeconomic status as predictors of adequate knowledge of prenatal diagnostic procedures as has been shown in previous studies [11,19,28,29] . Our results also indicate that women from minority ethnic groups and low socioeconomical status did not have negative attitudes towards genetic testing, but rather lower rates of informed choice, as has been previously reported [14,30,31] . It is noteworthy that among the 354 women who were interviewed, 252 (71.2%) were already aware of amniocentesis or CVS before the present gestation via friends, TV/press or due to family history.…”
Section: Discussionsupporting
confidence: 83%
“…Higher education levels, being of Asian ethnicity, having a history of infertility, and previous uptake of CVS or amniocentesis were significantly associated with increased likelihood to elect at least one invasive diagnostic prenatal test. This is consistent with previous studies that found higher uptake of invasive testing amongst women who had higher education levels 18,20 or were of Asian or Caucasian ethnicity. [18][19][20][21] On the other hand, lower education levels and being of Hispanic, Asian Indian, or mixed ethnicity were associated with choosing no testing for all conditions, a finding that is also consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies that found higher uptake of invasive testing amongst women who had higher education levels 18,20 or were of Asian or Caucasian ethnicity. [18][19][20][21] On the other hand, lower education levels and being of Hispanic, Asian Indian, or mixed ethnicity were associated with choosing no testing for all conditions, a finding that is also consistent with previous studies. [18][19][20][21] Prior personal experience with prenatal screening or testing played an important role in the decision to obtain information regarding microdeletion and microduplication syndromes.…”
Section: Discussionsupporting
confidence: 93%
“…Available researches on the determinants of PGTs have looked at (1) the attitudes of women and their partners, [7][8][9][10][11][12] (2) religious beliefs and women's attitudes towards termination of pregnancy, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and (3) women's racial-ethnic background. [32][33][34][35][36] From a cohort study of Italian women at risk because of advanced maternal age, the key determinant factor which influenced choice regarding amniocentesis was the preexisting view that the women had towards such a procedure. After receiving abnormal ultrasound findings, it was observed that women in favour of amniocentesis were more likely to ask for the test than women showing a negative attitude towards this practice.…”
Section: Introductionmentioning
confidence: 99%